The Impact of Reopening Zheng He’s Maritime Silk Road through One Belt One Road Policy on Indonesia–China Cooperation - Adibrata, Jordan Aria; Azis, Azrul; Khairi, Naufal Fikhri (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2020)
The aim of this article is to explain the impact of reopening the maritime silk route that was previously discovered by Admiral Zheng He which affecting the cooperation relations between Indonesia and China in the last few years. The line was reopened in 2013 in the Chinese OBOR policy with the name “21st Country Maritime Silk Road” (a new maritime silk route) that connects countries in Asia, Africa, and Europe, including Indonesia which in 2017 agreed to participate in inside it. The research question is;